A STUDY OF LEPTIN & LIPID PROFILE IN A SAMPLE OF IRAQI PATIENTS WITH KNEE OSTEOARTHRITIS. - Turki, Kismat M.; Alosami, Mohammed H.; Abdul-Qahar, Zina H. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: New data suggests that joint damage in Knee Osteoarthritis (KOA) may be caused by systemic factors like adipose tissue products; Adipokines, which may provide ametabolic link between obesity & KOA. Recently, one of the known adipokines named LEPTIN has been linked to KOA because it can be detected in serum & synovial fluid ofpatients with KOA.Objective: To evaluate the contribution of Leptin & serum lipids to the pathophysiology of Osteoarthritis in Iraqi patients with Knee OA.Subjects& Methods: The study was carried on 90 subjects divided into four groups: Knee Osteoarthritis cases group (n=60). Control group (n=30). Obese subjects group (n=60).Non-obese subjects group (n=30). KOA cases were diagnosed clinically whereas obesity was specified by BMI ≥25kg/m2. For all subjects studied measurements of fasting serum leptin and lipid profile have been done.Results: Mean serum leptin level was significantly higher in KOA cases compared to control group (P